A longitudinal study to assess the impact of exercise on clinical, biochemical, and anthropometric parameters among the type 2 diabetes patients of South India - Sukla, Pradeep (Avicenna J Med, 2015)
AIM: Aim of the study isto assess the scope of physical activity among type 2 diabetes mellitus (T2DM) patients residing in an urban area of SouthIndia. MATERIALS AND METHODS: A longitudinal interventional study was conducted for a period of 8months (January 2014–August 2014) among patients of T2DM accessing the healthcare services at an Urban Health and Training Center (UHTC) of a Medical College located in Kancheepuram district, Tamil Nadu. Universal sampling method was employed and all diagnosed T2DM patients attending UHTC during the month of January were enrolled in the study provided they satisfied the inclusion and exclusion criteria. Overall 151 participants were considered for final analysis and all of them were subjected to indulge in moderate type of aerobic exercise in the form of brisk walking for 2.5 h spread over a period of 1 week, for the next 6months. Before and after the exercise regimen, cases were subjected to clinical evaluation, measurement of weight and waist circumference, and estimation of fasting and postprandial blood sugar; and the results were compared with the baseline estimates. The associations were tested using paired t-test for continuous (mean ± standard deviation ( SD)) variables. RESULTS: Majority (86, 57%) of the diabetics were from the age group of 40–60 years with a definite female preponderance (82/151) in contrast to males (69/151). A significant reduction in both fasting and postprandial sugar was observed before and after the exercise. However, from the perspective of the weight and waist circumference, although a reduction was observed, the association was not statistically significant. CONCLUSION: The findings of the present longitudinal study suggest that compliance with moderate type of physical activity can significantly improve the fasting and postprandial blood sugar, apart from reduction in weight of T2DM patients.